Immune systems biology: immunoprofiling of cells and molecules - Aaron B. Kantor; Susan E. Alters; Karen Cheal; Louis J. Dietz (BioTechniques, 2004)
White blood cells and their secreted products are key elements of immune systems biology that are important indicators of patient health and disease. We have developed the SurroScan™ microvolume laser scanning cytometer to immunoprofile hundreds of variables, including cell populations, cell surface antigens, and intracellular molecules in antibody-based assays on small samples (about 1 mL) of whole blood, processed blood, or other fluids without cell purification or washing steps. The system enables high-throughput, robust and automated data capture and analysis. We demonstrate the utility of this immunoprofiling technology platform by surveying patient samples before and after glucocorticosteroid administration and show both the expected and novel response characteristics. This system complements recent advances in genomic and proteomic approaches to disease prediction and monitoring.